2015
DOI: 10.36607/refacer.v4i1.3373
|View full text |Cite
|
Sign up to set email alerts
|

CONDIÇÕES HIGIÊNICO-SANITÁRIAS DO MEL PRODUZIDO POR Apis melífera NO ESTADO DO MARANHÃO

Abstract: Introdução: O mel é um produto de excelente qualidade nutricional e muito utilizado também por suas propriedades medicamentosas. É produzido por abelhas a partir do néctar das flores ou exsudatos sacarínicos das partes vivas das plantas, que elas coletam, transformam, combinam com substâncias específicas e estocam nas colmeias. Objetivos: Avaliar a qualidade higiênico-sanitária de 30 amostras de méis de Apis mellifera produzidos no Estado do Maranhão no período de novembro de 2005 a fevereiro de 2006. Metodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…Coliform are a group of microorganisms present in the human and animal intestines, which do not represent a direct risk, but can serve as indicators of the presence of pathogenic microorganisms such as Enterobacter and Klebsiella in contaminated foods (Sousa, 2006). In general, these microorganisms are not found in honey (Holanda et al, 2013;Lima et al, 2015;Fernandez et al, 2017), thus not differing from what was found in this study.…”
Section: Microorganisms That Deteriorate Honeycontrasting
confidence: 50%
“…Coliform are a group of microorganisms present in the human and animal intestines, which do not represent a direct risk, but can serve as indicators of the presence of pathogenic microorganisms such as Enterobacter and Klebsiella in contaminated foods (Sousa, 2006). In general, these microorganisms are not found in honey (Holanda et al, 2013;Lima et al, 2015;Fernandez et al, 2017), thus not differing from what was found in this study.…”
Section: Microorganisms That Deteriorate Honeycontrasting
confidence: 50%